Computational vademecums for real‐time simulation of surgical cutting in haptic environments. (1st April 2016) - Quesada, Carlos; González, David; Alfaro, Iciar; Cueto, Elías; Chinesta, Francisco
Summary: A new method for the real‐time simulation of surgical cutting in haptic environments is presented. It is based on the intensive use of computational vademecums, that is, a sort of computational parametric meta‐model, which is computed offline and only evaluated online. Therefore, the necessary time savings are obtained, allowing for feedback responses on the order of kilohertz. Such a high‐dimensional, parametric solution of the problem is computed by employing proper generalized decomposition for the offline phase of the method, along with X‐FEM techniques for the incorporation of the discontinuities in the displacement field after cutting, in the online phase. A thorough description of the proposed method, along with examples of its performance in the simulation of corneal surgery, are provided. Copyright © 2016 John Wiley & Sons, Ltd.